2006
DOI: 10.1002/ajh.20786
|View full text |Cite
|
Sign up to set email alerts
|

De novo CD5+ diffuse large B cell lymphoma with basophilia in the peripheral blood: Successful treatment with autologous peripheral blood stem cell transplantation

Abstract: Basophils play an important role in allergic inflammation and are pathologically related to hematological disturbances, such as iron deficiency anemia and myeloproliferative disorders; however, they are only rarely encountered in lymphoid malignancies. Here, we report the case of a 33-year-old man with a bulky mass of the small intestine, multiple paraaortic lymphoadenopathy, pleural effusion, and ascites, who was diagnosed as a case of de novo CD5+ diffuse large B cell lymphoma (DLBCL). This patient showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
(23 reference statements)
1
2
0
Order By: Relevance
“…[1] The significantly increased absolute neutrophil count in anemic patients in the present study could possibly be due to compensatory activity due to inhibition in the capability to phagocytose. [2][3][4][5][6] In the present study, significant lymphopenia in anemic group is well correlated with some studies done in the past. The lymphopenia could be due to reduction in the lifespan of lymphocytes secondary to oxidative damage.…”
Section: Discussionsupporting
confidence: 85%
“…[1] The significantly increased absolute neutrophil count in anemic patients in the present study could possibly be due to compensatory activity due to inhibition in the capability to phagocytose. [2][3][4][5][6] In the present study, significant lymphopenia in anemic group is well correlated with some studies done in the past. The lymphopenia could be due to reduction in the lifespan of lymphocytes secondary to oxidative damage.…”
Section: Discussionsupporting
confidence: 85%
“…This study confirms the poor prognosis of de novo CD5+ DLBCL in a large multi-center cohort despite initial rituximab-containing chemotherapy and suggests that stem cell transplantation fails to salvage the majority of these patients. However, Tokuhira M et al [33] reported a successful treatment with autologous peripheral blood stem cell transplantation (APBSCT), they described the clinical course of a young Japanese man with de novo CD5+ DLBCL who showed marked elevation of the PB basophil count, and documented the clinical results and suggested that some salvage therapy, including APBSCT, may have the potential to cure the condition. From all parts mentioned above, it is worthy of note that de novo CD5+ DLBCL is associated with higher proliferative activity and a poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Basophilia is extremely rare in patients with lymphoid lymphoma. Tokuhira et al reported an unusual case of a patient with de novo CD5+ lymphoma and basophilia . The basophil count never exceeded 1 × 10 9 /L and basophilia was not a key feature that leads the physician to diagnose the lymphoid neoplasm.…”
Section: Looking For a Neoplastic Basophiliamentioning
confidence: 99%